Tingkat Pendidikan dan Pengetahuan Ibu Hamil dengan Status Anemia - Filius Chandra; Dini Dini Junita; Tina Yuli Fatmawati (UIMA Press, 2019)
Abstract Introduction: Pregnancy is the most important for fetal growth. The need for iron also increases with increasing gestational age. Inadequate nutritional intake in pregnant women can cause anemia. Mothers with malnutrition can increase the risk of miscarriage and perinatal death. High education is expected to increase knowledge. Nutritional knowledge can help someone learn how to store, process and use quality food ingredients for consumption. Objective: The purpose of this study was to determine the relationship of education and knowledge on the status of anemia in pregnant women at the PuskesmasSimpang Kawat Kota Jambi. Method: This research is a correlative descriptive study with a cross-sectional approach. Sampling techniquesused in the sample is a total of 41 respondents, the data analysis used was Univariate and Bivariate analysis with Chi Square. Results: The results found a significant relationship between education and knowledge of respondents with anemia status of pregnant women with 0,000 (p <0.005). Conclusion: The importance of health education carried out about anemia during pregnancy so that complications do not occur after pregnancy.of the study conducted.